Cultural adaptation and content validation of the WHO BeSD framework for HPV vaccination in Pakistan: A two-phase Delphi and cognitive interview study - Khola Noreen; Samina Naeem Khalid; Mehreen Noor; Saba Maryam; Shahzad Ali Khan; Abdul Momin Rizwan Ahmad (PLoS ONE, 2026)
Background The BeSD Framework (Behavioral and Social Drivers of Vaccination), developed by the World Health Organization, provides a structured approach to understanding the behavior and social drivers of vaccine uptake. However, it’s direct use in diverse cultural backgrounds especially in the context of HPV vaccination, is not yet established. Therefore, this study aimed to culturally adapt and establish content validity of the BeSD framework for assessing behavioral and social drivers of Human papillomavirus (HPV) vaccination in Pakistan. Methods A two-phase multi-method cross-cultural adaptation with expert content validation and cognitive interviews was used following the emic–etic paradigm and globally accepted Beaton’s cross-cultural adaptation guidelines. The initial items of the BeSD-HPV tool were translated into Urdu through forward–backward translation and expert synthesis. Content validity was assessed using a two-round Delphi method with ten multidisciplinary experts, who rated items on a four-point relevance and clarity scale. Consensus was a priori defined as item-level content validity index scores of ≥0.80. A scale-level content validity index score was also calculated. Response-process validity was then evaluated through cognitive interviews with 30 caregivers of adolescent girls using think-aloud and probing techniques to assess comprehension and cultural appropriateness. Results Ten experts participated in both rounds of the online Delphi study. At the completion of the study, out of the initial 75 items, two items were dropped in round one and three items were dropped in round 2. Out of the total 73 left in round 1, 28 items were accepted by all experts without revision, 42 were revised in rounds 2 and 3 were dropped in round 2, resulting in a 70-item BeSD-HPV tool. The scale-level content validity index score for the final 70-item instrument was 0.96. Cognitive interviews using the think-aloud technique and probing were conducted with parents/caregivers of girls aged 9–16 years. A total of 30 interviews were conducted. Seventeen items categorized as having minor or major issues were revised by the authors based on participant feedback to improve comprehension. Conclusion The adapted BeSD-HPV tool demonstrated strong content and response-process validity for the Pakistani context. This culturally sensitive instrument will support future large-scale studies to determine the construct validity and reliability of the BeSD-HPV, thereby providing a validated tool to assess drivers of HPV vaccine acceptance and inform future context-specific demand generation strategies.